Transient Confinement of CaV2.1 Ca2+-Channel Splice Variants Shapes Synaptic Short-Term Plasticity - Heck, Jennifer; Parutto, Pierre; Ciuraszkiewicz, Anna; Bikbaev, Arthur; Freund, Romy; Mitlöhner, Jessica; Andres-Alonso, Maria; Fejtová, Anna; Holcman, David; Heine, Martin (Neuron, 2019)
The precision and reliability of synaptic information transfer depend on the molecular organization of voltage-gated calcium channels (VGCCs) within the presynaptic membrane. Alternative splicing of exon 47 affects the C-terminal structure of VGCCs and their affinity to intracellular partners and synaptic vesicles (SVs). We show that hippocampal synapses expressing VGCCs either with exon 47 (CaV2.1+47) or without (CaV2.1Δ47) differ in release probability and short-term plasticity. Tracking single channels revealed transient visits (∼100 ms) of presynaptic VGCCs in nanodomains (∼80 nm) that were controlled by neuronal network activity. Surprisingly, despite harboring prominent binding sites to scaffold proteins, CaV2.1+47 persistently displayed higher mobility within nanodomains. Synaptic accumulation of CaV2.1 was accomplished by optogenetic clustering, but only CaV2.1+47 increased transmitter release and enhanced synaptic short-term depression. We propose that exon 47-related alternative splicing of CaV2.1 channels controls synapse-specific release properties at the level of channel mobility-dependent coupling between VGCCs and SVs.
CRIS-Team Scopus Importer:2019-07-09
Keywords: calcium channel; localization microscopy; nanodomain; presynapse; short-term plasticity; single particle tracking; surface mobility; synapse; synaptic transmission; vesicular release